Snowflake degeneration of a poly(methyl methacrylate) intraocular lens. Issue 1 (January 2017) - Patel, Hershel; Chaleff, Alec; Patel, Neil; Shah, Ankit; Patel, Chetan K.; Ferguson, David J.P.
Abstract : N/A: A 74‐year‐old pseudophakic woman presented with progressive declining vision in the left eye not improved with refraction. Uneventful extracapsular cataract extraction with insertion of an intraocular lens (IOL) in the left eye had been performed 20 years earlier. Slitlamp examination revealed an opacified IOL that was centered in the pupillary axis. An IOL exchange was performed, and the frosted IOL was examined via scanning electron microscopy (SEM). The central region between the anterior and posterior surfaces of the IOL showed numerous unusual fissures and appeared fractured rather than smoothly cut. This is consistent with snowflake degeneration of a poly(methyl methacrylate) (PMMA) IOL attributed to exposure to ultraviolet (UV) light. The peripheral optic is protected by the iris, so the central optic is affected most. Our findings support the hypothesis that snowflake degeneration of a PMMA IOL is due to UV light exposure. The opacifications were viewed through SEM.